Enabling multilingual retrieval of Arabic materials through Linked Open Data (LOD): Mechanisms & Challenges - Iman Khairy Weheba (22770305) (2025)
Open access to information in libraries is a fundamental pillar for promoting equitable knowledge access and global participation. Adopting the open movement enables cultural institutions and libraries to provide free access to information resources and also to publish their data on the open web, which contributes to system integration and improves retrieval. Therefore, Qatar National Library has initiated a project to publish its bibliographic and authority data as linked open data, supporting innovation in delivering a better user experience and creating opportunities for collaboration between Arab and foreign institutions in this field. This presentation intends to highlight this project and its main pecularities. تعد الإتاحة الحرة للمعلومات في المكتبات ركيزة أساسية لتعزيز الوصول المعرفي العادل والمشاركة العالمية. إن تبني الحركة المفتوحة يتيح للمؤسسات الثقافية والمكتبات الاتاحة الحرة لمصادر المعلومات كما يتيح أيضا نشر بياناتها على الويب المفتوح، مما يسهم في التكامل بين الأنظمة وتحسين الاسترجاع، لذلك شرعت مكتبة قطر الوطنية في تبني مشروع نشر بياناتها الببليوجرافية والاستنادية كبيانات مترابطة مفتوحة، مما يدعم الابتكار في توفير تجربة أفضل للمستخدم وفرص التعاون بين المؤسسات العربية والأجنبية في هذا المجال. يهدف هذا العرض التقديمي للتعريف بهذا المشروع وأهم جزئياته. Other Information Conference information: 36th Annual Conference of the Arab Federation for Libraries and Information (AFLI), 23-25 Nov 2025, Education City Student Center (Multaqa), Doha, Qatar License: https://creativecommons.org/licenses/by/4.0 See conference information: 36th Annual Conference of the Arab Federation for Libraries and Information (AFLI) https://ssl.eventilla.com/event/ryYPq/EN